Why Does Work Stress Occur in Nurses? - Kaira Devi; Priskila Hananingrum; Y. Denny A. Wahyudiono (Universitas Airlangga, 2023)
Introduction:Work stress can occur in many professions, including nursing, which is inseparable from individual characteristics. Inpatient is one of the units at Ploso Regional Public Hospital, Jombang, which has time-consuming work that requires observation on an ongoing basis. This study aimed to understand the relationship between individual characteristics, such as age, gender, marital status, working period, and personality type, with the level of work stress experienced by the inpatient installation unit nurses at Ploso Regional Public Hospital, Jombang. Methods: Observational descriptive study was applied with a cross-sectional design. Age, gender, marital status, working period, and personality type were the independent variables used in this study, while the dependent variable was work stress. The sample used was the total accessible population of nurses in the inpatient unit with 33 respondents. The data collection method used was a general questionnaire for personal variables (age, gender, marital status, working period), Personality Type Questionnaire for personality type, and Health and Safety Executive (HSE) Questionnaire for work stress. Data were analyzed using chi-square correlation and spearman correlation test. Results: In the inpatient installation unit, most nurses were male between the ages of 24-37, had a working period of less than five years, were married, and had type A personality. The individual characteristics which had a moderate relationship with work stress were age (Ï = 0.419), marital status (Ï = 0.461), and working period (Ï = 0.359). Gender (Ï = 0.246) and personality type (Ï = 0.179) had a weak relationship with work stress. Conclusion: Age, marital status, and working period had a moderate relationship with work stress, while gender and personality type had a weak relationship.